Pertumbuhan Bayam Kuning (Amaranthus blitum) dengan Pemberian Pupuk Organik Cair Tumbuhan Paku Acrostichum aureum, Nephrolepis biserrata, dan Stenochlaena palustris - Irwan Lovadi, Sri Mey Crisna Lumban Toruan, Mukarlina (Universitas Tanjungpura, 2015)
The amaranth (Amaranthus blitum) is a type of commonly cultivated spinach. The use of inorganic fertilizer for growing spinach needs to be reduced by using organicfertilizer for sustainable culture. The plant species which are abundant and potential to be used as the material for organic fertilizer are thefern weeds. The purpose of this research to determine the content of nutrient of the Organic Liquid Fertilizer (LOF) from ferns Acrosticum aureum, Nephrolepis biserrata, and Stenochaena palustris, as well as its effects on the growth of the amaranth. This research used a Completely Randomized Design (CRD) with 6 degrees of treatment. The analysis showed the value of As <0.010, Hg <0.004, Pb <0.040, Cd <0.020, Sn 0.010, C-Org 0.29 %, N 0.04 %, P 0.008 %, K 0.1%, Fe 18.09 ppm, Mn 6.98 ppm, Cu 0.53 ppm, Ca 49.34 ppm, Mg 169 ppm, S 28.03 ppm, and Zn 1.24 ppm. The ANOVA results showed that the LOF from ferns had significant effect on the plant height (F5.24 = 2.934, p = 0.033), number of leaves (F5.24 = 4.797, p = 0.04), number of lateral buds (F5.24 = 10.585, p = 0.0001),leaf breadth (F5.24 = 3.695, p = 0.013), and weight of wet root (F5.24 = 4.109, p = 0.008). The concentration of 75 ml/L had the highest effect on the parameters of the plant height and number of leaves. The concentration of 60 ml/L had the highest effect on the parameters of lateral buds and weight of wet roots. The concentration of 15 ml/L had the highest effect on the parameter of leaf breadth.